An auxetic nonlinear piezoelectric energy harvester for enhancing efficiency and bandwidth. (15th September 2021) - Chen, Keyu; Gao, Qiang; Fang, Shitong; Zou, Donglin; Yang, Zhengbao; Liao, Wei-Hsin
Graphical abstract: Highlights: Propose an auxetic nonlinear piezoelectric energy harvester. Utilize a pure mechanical structure to enhance both efficiency and bandwidth. Perform finite element analysis to analyse the performance of the harvester. Experimentally validate the proposed design and model and conduct parametric studies. Abstract: In this paper, we design and experimentally validate an auxetic nonlinear piezoelectric energy harvester. This harvester adopts a clamp-clamp beam with auxetic structures, which can improve the efficiency and bandwidth of the energy harvesting based on a pure mechanical structure without outer magnets or stoppers. Finite element analysis is performed to analyse the effects of the auxetic structures on the efficiency and nonlinearity of the energy harvester. The lumped parameter model is utilized to predict the performance of the energy harvester, which well matches the experimental results. In the experimental validation, at 0.1 g base acceleration, the power output of the two types of auxetic energy harvesters is 173% and 94% higher than the conventional nonlinear energy harvester. Besides, the bandwidths of the two types of auxetic energy harvesters are broadened by 1556% and 2142% compared with the linear systems.